Re-analysis of archaeobotanical remains from pre- and early agricultural sites provides no evidence for a narrowing of the wild plant food spectrum during the origins of agriculture in southwest Asia - Wallace, M; Jones, G; Charles, M; Forster, E; Stillman, E; Bonhomme, V; Livarda, A; Osborne, C; Rees, M; Frenck, G; Preece, C (Springer Verlag, 2018)
Archaeobotanical evidence from southwest Asia is often interpreted as showing that the spectrum of wild plant foods narrowed during the origins of agriculture, but it has long been acknowledged that the recognition of wild plants as foods is problematic. Here, we systematically combine compositional and contextual evidence to recognise the wild plants for which there is strong evidence of their deliberate collection as food at pre-agricultural and early agricultural sites across southwest Asia. Through sample-by-sample analysis of archaeobotanical remains, a robust link is established between the archaeological evidence and its interpretation in terms of food use, which permits a re-evaluation of the evidence for the exploitation of a broad spectrum of wild plant foods at pre-agricultural sites, and the extent to which this changed during the development of early agriculture. Our results show that relatively few of the wild taxa found at pre- and early agricultural sites can be confidently recognised as contributing to the human diet, and we found no evidence for a narrowing of the plant food spectrum during the adoption of agriculture. This has implications for how we understand the processes leading to the domestication of crops, and points towards a mutualistic relationship between people and plants as a driving force during the development of agriculture.